Evaluation Of The Buku Pokok Pemakaman Application In Supporting Smart Governance Using The System Usability Scale (SUS) (A Case Study At The Department Of Population And Civil Registration Of Magetan Regency) - Yulinda Seven Ningtyas; Ervin Yohannes (Universitas Negeri Surabaya, 2026)
Abstract—Buku Pokok Pemakaman Application is a web-based system developed by the Population and Civil Registration Office of Magetan Regency to support the management of death data. This study aims to evaluate the usability of the application using the System Usability Scale (SUS) method and to provide improvement recommendations based on the evaluation results. The study involved 112 respondents, who are village and sub-district (desa and kelurahan) operators acting as active users of the application. Data were collected through task-scenario testing to measure effectiveness and efficiency, distribution of the SUS questionnaire to measure user satisfaction, and interviews to identify problems in using the application. The data were analyzed using the effectiveness, efficiency, and System Usability Scale (SUS) metrics. The results show an effectiveness level of 98.98%, categorized as very effective. An efficiency value of 0.121 goals/sec indicates that users were able to complete tasks well. Meanwhile, the SUS evaluation obtained an average score of 68.59, which falls into Grade C, with a High Marginal acceptance level and an OK adjective rating. These results indicate that the application has met the aspects of effectiveness and efficiency but still requires improvement to increase user satisfaction. Based on the evaluation results, this study produced five interface improvement recommendations, realized in the form of mockups referring to the Google Material Design guidelines. Kata Kunci— usability, System Usability Scale (SUS), buku pokok pemakaman, smart governance, information system evaluation.